2012
DOI: 10.1111/j.1469-7610.2012.02609.x
|View full text |Cite
|
Sign up to set email alerts
|

Neural mechanisms of emotion regulation in childhood anxiety

Abstract: Anxious children appeared to show increased cortical activation regardless of the emotional content of the stimuli. Anxious children also showed greater medial-frontal activity regardless of task demands and response accuracy. Taken together, these findings suggest indiscriminate cortical processes that may underlie the hypervigilant regulatory style seen in clinically anxious individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
64
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(87 citation statements)
references
References 69 publications
13
64
1
Order By: Relevance
“…() found greater N2 activation for more compared to less non‐clinically anxious college students using a go/no‐go task. Hum et al ., () found greater N2 activation for clinically anxious children than non‐anxious children using a go/no‐go task.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…() found greater N2 activation for more compared to less non‐clinically anxious college students using a go/no‐go task. Hum et al ., () found greater N2 activation for clinically anxious children than non‐anxious children using a go/no‐go task.…”
Section: Discussionmentioning
confidence: 96%
“…Given that previous studies have shown greater (more negative) N2 and ERN activation for anxious participants than non‐anxious participants (e.g. Hum et al ., ; Ladouceur et al ., ; Lamm, Granic, Zelazo & Lewis, ; Righi et al ., ), we predicted that BI would be associated with both greater N2 activation and more source‐space activation. Furthermore, given that greater ERN activation moderated the BI–anxiety association in prior work (McDermott et al ., ), we also predicted the same pattern of results in the current study.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that inhibitory processes are less impaired in MIXED because this subtype may be associated with an overcontrolled style of self‐regulation. Studies in anxious populations show that these children perform similarly, and, at times, even better, than their peers on tasks requiring inhibitory control (Günther, Holtkamp, Jolles, Herpertz‐Dahlmann, & Konrad, ; Hum, Manassis, & Lewis, ).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, we did not find a group effect for the P100. Previous research (on emotional categorization, emotional Stroop, oddball, or dot probe tasks) consistently reported higher P100 amplitudes to facial stimuli in adults and children with SAD compared to controls (e.g., Hum et al, 2013;Kolassa et al, 2009Kolassa et al, , 2007Rossignol et al, 2013. In the current study, we used a free viewing paradigm, which is why the comparability to previous studies is restricted.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates an intensity amplification bias by SAD patients also on the electrocortical level. Previous research repeatedly showed that the enhanced sensitivity to facial expressions in social anxiety is not restricted to negative facial expressions (e.g., Hum, Manassis, & Lewis, 2013;Moser et al, 2008;Mühlberger et al, 2009;Rossignol, Philippot, Bissot, Rigoulot, & Campanella, 2012).…”
Section: Discussionmentioning
confidence: 99%